Dispensasi Perkawinan Perspektif Undang-Undang Perlindungan Anak dan Maqasid Al-Shari’ah - Zamroni Wafa (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2023)
Abstract The marriage age requirement after Law No. 16 of 2019 concerning Marriage was passed became 19 years for prospective husbands or wives resulting in an increase in filings for marriage dispensation at the Religious Courts. From 2019 until now, requests for dispensation for underage marriages in Indonesia continue to grow every year. The increase in the problem of underage marriages occurred during the Covid-19 pandemic, it was women who experienced many underage marriages. The purpose of the authors to carry out this research is to find out the dispensation of marriage according to the Marriage Law, the Child Protection Law and in a review of maqÄshid al-sharÄ«'ah. This type of research is a qualitative-descriptive analysis. Data collection was carried out using library research using the documentation method in the form of tracking documents in the form of journals, books, and online media that correlated with the research focus. The results of this study found that the dispensation of marriage in the Marriage Law and legislation in Indonesia is strictly regulated through a trial mechanism in court to obtain a permit. The judge's considerations in determining the Dispensation of Marriage, among others, refer to maqÄshid al-shari'ah, namely to maintain religion, soul, property, lineage, and reason. Keywords: Marriage Dispensation, Child Protection Law, MaqÄshid al-Shari'ah